ANALISIS PENYAJIAN PANDUAN PEMBELAJARAN LITERASI SAINS DALAM BUKU TEMATIK TERPADU KELAS IV KURIKULUM 2013 - Rahayu, Ai Hayati (Mimbar Sekolah Dasar, 2014)
This study aims at determining the extent to which aspects of scientific literacy that consist of science as a body knowledge, science as the way of investigating, science as the way of thinking, and interaction among of science technology and society presented in the teacher book . The source of research data is an integrated thematic teacher book grade IV theme 3 concerned about the living creatures. The research study uses descriptive analysis to describe the aspects of scientific literacy. The analysis uses instruments that adopted from Chiapetta, Sethna and Filman in Padayache. The result of the analysis showed that two important findings: 1) aspect of science as a body of knowledge having the highest percentage of the three aspects; 2) Not all of indicators of the aspects found in the teacher book guide. Keywords: teacher books, scientific literacy, quantitative analysis, curriculum 2013.